KONSEP APIK DALAM KOREOGRAFI WAYANG BABAR - Hadi, Sri (Sekolah Pascasarjana UGM, 2014)
This article is titled âKONSEP APIK DALAM KOREOGRAFI WAYANG BABARâ. It aims to explainchoregraphic concept of wayang babar. In order to make it possible the article needs the medium of cocontinuity and development of traditional wayang orang. The concept of APIK is Artistic, performance,inovatif, and communicative. The APIK concept is arts workers of wayang babarâs choregraphicfor the future of wayang wong show. Furthermore, the play is shown by wayang babar of inovatifperformance of wayang babar from the modification of wayang wong, using the story, dance, and stageto choregraphy concept.